2003
DOI: 10.2165/00003088-200342130-00001
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Effects on Drug Metabolism and Transport

Abstract: Metabolic food-drug interactions occur when the consumption of a particular food modulates the activity of a drug-metabolising enzyme system, resulting in an alteration of the pharmacokinetics of drugs metabolised by that system. A number of these interactions have been reported. Foods that contain complex mixtures of phytochemicals, such as fruits, vegetables, herbs, spices and teas, have the greatest potential to induce or inhibit the activity of drug-metabolising enzymes, although dietary macroconstituents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
125
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(128 citation statements)
references
References 145 publications
2
125
0
1
Order By: Relevance
“…It has been reported that activity of CYP3A4 enzyme is particularly sensitive to dietary effects [57]. Although the potential effect of food on sunitinib pharmacokinetics was not supported by the phase I study in healthy subjects, in which no difference of sunitinib and SU12662 pharmacokinetics was found between patients with single dose of sunitinib after either 10-hour fast or a high-fat meal, the effect of long-term cooking habit, such as the frequently used CYP3A4-inhibiting spices [58], could not be ignored.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that activity of CYP3A4 enzyme is particularly sensitive to dietary effects [57]. Although the potential effect of food on sunitinib pharmacokinetics was not supported by the phase I study in healthy subjects, in which no difference of sunitinib and SU12662 pharmacokinetics was found between patients with single dose of sunitinib after either 10-hour fast or a high-fat meal, the effect of long-term cooking habit, such as the frequently used CYP3A4-inhibiting spices [58], could not be ignored.…”
Section: Discussionmentioning
confidence: 99%
“…[10] Isocaloric diets with a high fat percentage in healthy volunteers did not demonstrate an effect on drug metabolism. [11] However, these isocaloric diets probably did not induce steatotic changes in the liver.…”
Section: Introductionmentioning
confidence: 93%
“…CYP3A4 metabolizes about 50% of all drugs. Consequently, substances that induce or inhibit CYP3A4 are of particular signifi cance for the drug interactions [9,[23][24][25].…”
Section: Presystemic Clearancementioning
confidence: 99%